Overall equipment effectiveness analysis of power magnetic inductor production line at BI technologies sdn. bhd. - Nur Syuhadah, Abdul Wahab (2017)
Overall Equipment Effectiveness (OEE) is a powerful metric technique of manufacturing performance incorporating measures of the utilization, yield and efficiency of a process, machine or manufacturing line. It considers all important measures of productivity. A study was carried out to improve the existing OEE at BI Technologies SDN BHD by reduce unplanned downtime losses on equipment failures and tooling damage to maximize the productivity. Before obtaining the data to calculate the existing OEE value, the product or process that have highest defect need to be identified which is HA00-05587LFVT at Power Magnetic Inductor area. The methods used to analyze these various causes were Cause and Effect diagram, to find the cause affecting the problem that occurs on the production line, Pareto Diagram to find the critical problem that affect the production line, control chart to find the out of control point and 5W1H questions to proposed the recommendation. After knowing the causes of various activities that leads to high downtime rate, then recommendations for OEE improvements from existing OEE which is 71.33% to 79.55% for the second revised of OEE. Thus, from the existing to world class ranking OEE there are improvement by 11.52%. For the recommendation BI Technologies should implemented and monitor of planned scheduled for machine maintenance to decrease the downtime rate, so the production yield target can achieve.